Pengaruh Kontribusi Pajak Kendaraan Bermotor, Bea Balik Nama Kendaraan Bermotor Dan Jumlah Penduduk Terhadap Pendapatan Asli Daerah Kabupaten Sarolangun Tahun 2016-2020 - Wage Suratman; Elyanti Rosmanidar; Yuliana Safitri (Pusat Riset dan Inovasi Nasional, 2023)
This thesis aims to determine the effect of motor vehicle tax contributions, motor vehicle transfer fees and the number of residents on the local revenue of Sarolangun Regency in 2016-2020. This study uses independent variables, namely the contribution of motor vehicle tax, motor vehicle transfer fees and population. the dependent variable is local revenue. The data used in this study are primary data and secondary data. The primary data in this study were obtained directly from the research location, namely the regional financial and asset planning agency for Sarolangun Regency, and the one-roof administrative system (samsat) for Sarolangun Regency. and secondary data, namely reports on the realization of local own-source revenues, motorized vehicle taxes and transfer fees for motorized vehicles, and statistical data. 2016 is used to compare 2017 to 2020. This research is quantitative. Statistical methods using multiple linear regression analysis, t test, f test, and analysis of the coefficient of determination. The results of this study indicate that the contribution of motor vehicle tax, motor vehicle transfer fee and total population have no effect on local revenue. By using the F test it was found that the independent variables did not have a simultaneous effect on the dependent variable.